Negative electrode material and preparation method and application thereof

By combining gradient cladding and graphite carrier on the negative electrode material, the performance and stability problems of traditional cladding methods under high-rate charging and discharge conditions are solved, and efficient battery performance improvement and safety enhancement are achieved. At the same time, it reduces production costs and is suitable for industrial applications.

CN119297227APending Publication Date: 2025-01-10ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411334464.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The traditional negative electrode material coating method has slow charging speed and poor cladding stability under high-rate charging and discharge conditions, resulting in battery performance and safety problems, and faces cost and process complexity challenges from material structure optimization.

Method used

Using the combination of carrier and gradient cladding, soft carbon materials decrease from the inside to the outside, and hard carbon materials increase from the inside to the outside. Combined with graphite carrier and funnel-shaped channel structure, the cladding layer is prepared through the spraying process to form an optimized Conductivity and structural matching.

Benefits of technology

It improves the reversible capacity, rate performance and cycle stability of the negative electrode material, enhances the charging and discharging efficiency and safety performance of the battery, reduces production costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057887160000141
    Figure BDA0005057887160000141
  • Figure BDA0005057887160000151
    Figure BDA0005057887160000151
  • Figure BDA0005057887160000152
    Figure BDA0005057887160000152
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method and application thereof. The negative electrode material comprises a carrier and a coating layer at least partially covering the surface of the carrier, the coating layer contains a soft carbon material and a hard carbon material, the content of the soft carbon material is gradually reduced from inside to outside, and the content of the hard carbon material is gradually increased from inside to outside. The structure has good reversible capacity, rate and cycle performance, and the cycle performance, rate performance and safety performance of the material are improved. The invention also provides a preparation method and application of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a negative electrode material and a preparation method and application thereof. Background Art

[0002] In battery technology, the selection and modification of negative electrode materials is the key to improving battery performance. Traditional methods of modifying negative electrode materials mainly include soft carbon coating and hard carbon coating. Although these two methods have improved the performance of negative electrode materials to a certain extent, they also have their own limitations.

[0003] Soft carbon coating is a method of coating a soft carbon material with good conductivity on the surface of the negative electrode material. Soft carbon has good conductivity, which enables electrons to transfer more efficiently in the negative electrode material during the charging and discharging process of the battery, thereby improving the overall performance of the battery. However, soft carbon coating also has some significant shortcomings. First, the charging performance is insufficient. Although soft carbon has good conductivity, its conductivity may be bottlenecked at high current density. Especially under high-rate charge and discharge conditions, soft carbon-coated negative electrode materials may face the problem of slow charging speed. Secondly, the stability of the coating layer is not ideal. The soft carbon coating layer may fall off or be damaged during repeated charging and discharging, thereby affecting the long-term stability and cycle life of the battery. Hard carbon coating is to coat a hard carbon material with high hardness and poor conductivity on the surface of the negative electrode material. The advantage of hard carbon coating is that it can provide better mechanical protection and reduce structural damage to the negative electrode material. However, hard carbon coating also has the disadvantages of poor conductivity and poor comprehensiveness. Specifically, the conductivity of hard carbon is generally poor, which will lead to a decrease in the efficiency of electron transfer during the charge and discharge process of the battery, thereby affecting the power performance of the battery. The hard carbon coating has a weak bonding force with the substrate and is prone to interface defects. Such defects may lead to the occurrence of side reactions, further affecting the performance and safety of the battery. In addition, due to the poor bonding between the hard carbon coating and the negative electrode material, structural defects and side reactions may be induced. These problems not only affect the transfer of electrons, but may also make it difficult to deintercalate and extract lithium ions, thereby reducing the capacity and life of the battery.

[0004] In order to overcome the shortcomings of the above-mentioned traditional coating methods, researchers began to explore optimization starting from the material structure itself. It is expected that by deeply optimizing the structure of the negative electrode material, the performance of the battery can be improved without relying on a single coating material. For example, optimizing the microstructure of the negative electrode material, such as by adjusting the porosity, particle size and morphology, can improve the transmission rate and storage capacity of lithium ions. This optimization can effectively improve the specific capacity and charge and discharge efficiency of the material. However, although the research on material structure optimization provides a new direction for improving battery performance, it still faces challenges in cost, complex processes and unstable performance in practical applications. Therefore, a new negative electrode material still needs to be developed. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a negative electrode material with good reversible capacity, rate and cycle performance, and improves the cycle performance, rate performance and safety performance of the material.

[0006] The invention also provides a method for preparing the negative electrode material.

[0007] The invention also provides a lithium ion battery.

[0008] The first aspect of the present invention provides a negative electrode material, including a carrier and a coating layer covering the carrier, wherein the coating layer contains soft carbon material and hard carbon material, the content of the soft carbon material gradually decreases from the inside to the outside, and the content of the hard carbon material gradually increases from the inside to the outside.

[0009] One of the technical solutions of the present invention regarding the negative electrode material has at least the following beneficial effects:

[0010] The negative electrode material of the present invention comprises a coating layer containing a soft carbon material and a hard carbon material, wherein the content of the soft carbon material gradually decreases from the inside to the outside, and the content of the hard carbon material gradually increases from the inside to the outside. The structure has good reversible capacity, rate and cycle performance, and improves the cycle performance, rate performance and safety performance of the material.

[0011] Soft carbon has better bonding with the substrate and better conductivity, while hard carbon has a larger disorder and interlayer spacing than soft carbon, which is beneficial to improving the charging performance of the material. The gradient structure can make the main material more compatible with the coating layer, preventing structural cracking problems caused by the large difference between the coating layer and the main material in high temperature and high pressure environments.

[0012] The negative electrode material of the present invention, combined with the advantages of soft and hard carbon coating layers, can effectively improve the conductivity of the material, enhance the lithium ion desolvation ability, enhance the charging performance, and improve the temperature coefficient (25°C discharge capacity / 45°C discharge capacity). It has good charge and discharge cycle performance and rate performance, and has broad application prospects in the field of energy storage.

[0013] According to some embodiments of the present invention, the support comprises a graphite support.

[0014] According to some embodiments of the present invention, pores are distributed in the coating layer.

[0015] According to some embodiments of the present invention, the channel is a funnel-shaped structure that is narrow inside and wide outside.

[0016] According to some embodiments of the present invention, the pore size b of the pore channel, the thickness h of the coating layer, and the particle size a of the carrier satisfy the relationship: b = h / 100 + a × 10 -5 , where a ranges from 5 μm to 10 μm, and h ranges from 30 nm to 80 nm.

[0017] The second aspect of the present invention provides a method for preparing the negative electrode material of the first aspect of the present invention, comprising the steps of mixing a soft carbon source and a hard carbon source to prepare a coating agent, and then coating the carrier by spraying.

[0018] A technical solution in the method for preparing negative electrode materials of the present invention has at least the following beneficial effects:

[0019] The preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize. The simple preparation process also greatly improves the consistency and repeatability of production. This gradient material with a coating layer will promote the application of negative electrode materials in the lithium ion battery industry.

[0020] According to some embodiments of the present invention, the spraying time t and the mass percentage X of the soft carbon source in the coating agent and the mass percentage Y of the hard carbon source in the coating agent satisfy the relationship: X=1 / (t+1), X+Y=1.

[0021] According to some embodiments of the present invention, the soft carbon source includes at least one of polyurethane resin, styrene resin, phenolic resin, epoxy resin, amide resin, polyimide resin, silicone resin, cycloolefin resin and asphalt.

[0022] The third aspect of the present invention provides a lithium ion battery, comprising the negative electrode material of the first aspect of the present invention or the negative electrode material prepared by the method of the second aspect of the present invention.

[0023] One of the technical solutions of the present invention regarding lithium-ion batteries has at least the following beneficial effects:

[0024] The lithium ion battery of the present invention has all the beneficial effects of the negative electrode material due to the use of the negative electrode material of the present invention, specifically:

[0025] In terms of improving conductivity, due to the presence of soft carbon materials in the coating layer, the conductivity of the battery is significantly improved, which helps to improve the battery's charging and discharging efficiency and power performance.

[0026] In terms of enhancing cycle performance, the gradient coating structure makes the material and the substrate more compatible, reducing the structural cracking problem caused by the mismatch between the coating layer and the substrate, thereby increasing the cycle life of the battery.

[0027] In terms of optimizing rate performance, the gradual incremental design of hard carbon materials helps to improve the charging performance of the materials, allowing the battery to maintain a higher capacity and stability during high-rate discharge.

[0028] In terms of improving temperature stability, by improving the temperature coefficient, the discharge capacity of the battery under different temperature conditions (such as 25°C and 45°C) maintains good consistency, enhancing the battery's temperature adaptability.

[0029] In terms of improving safety performance, the design of the gradient coating reduces the safety hazards caused by the difference in properties between the coating and the substrate, and exhibits better stability under high temperature and high pressure environments.

[0030] The above improvements enable lithium-ion batteries containing the negative electrode material to have better overall performance and broader application prospects in the field of energy storage. DETAILED DESCRIPTION

[0031] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0032] In the first aspect, some embodiments of the present invention provide a negative electrode material, including a carrier and a coating layer covering the carrier, the coating layer containing soft carbon material and hard carbon material, the content of the soft carbon material gradually decreases from the inside to the outside, and the content of the hard carbon material gradually increases from the inside to the outside.

[0033] It can be understood that the negative electrode material of the present invention contains soft carbon material and hard carbon material in the coating layer, the content of soft carbon material gradually decreases from the inside to the outside, and the content of hard carbon material gradually increases from the inside to the outside. This structure has good reversible capacity, rate and cycle performance, and improves the cycle performance, rate performance and safety performance of the material.

[0034] Soft carbon has better bonding with the substrate and better conductivity, while hard carbon has a larger disorder and interlayer spacing than soft carbon, which is beneficial to improving the charging performance of the material. The gradient structure can make the main material more compatible with the coating layer, preventing structural cracking problems caused by the large difference between the coating layer and the main material in high temperature and high pressure environments.

[0035] The negative electrode material of the present invention, combined with the advantages of soft and hard carbon coating layers, can effectively improve the conductivity of the material, enhance the lithium ion desolvation ability, enhance the charging performance, and improve the temperature coefficient (25°C discharge capacity / 45°C discharge capacity). It has good charge and discharge cycle performance and rate performance, and has broad application prospects in the field of energy storage.

[0036] In combination with the first aspect, in some embodiments of the present invention, the support includes a graphite support.

[0037] When the carrier of the negative electrode material is a graphite carrier, first of all, graphite has excellent electrical conductivity. As a carrier of the negative electrode material, it can significantly improve the overall conductivity of the battery. Graphite carriers can effectively improve the electronic conduction of the battery during high-rate charge and discharge, thereby improving the power performance and charging speed of the battery. Secondly, the graphite carrier itself has a high theoretical specific capacity (about 372mAh / g), and combined with the soft carbon and hard carbon materials in the coating layer, it can further improve the overall specific capacity of the negative electrode material. This design can make full use of the electrochemical properties of graphite to achieve higher energy density. Third, as the basis of the negative electrode material, the graphite carrier can provide good structural support to prevent the negative electrode material from undergoing significant volume expansion or contraction during the charge and discharge process. Combined with the gradient design of the coating layer, it can effectively reduce the volume change of the material and improve the cycle stability and life of the material. Fourth, graphite has good thermal stability and can maintain stable electrochemical properties under high temperature conditions. Combined with soft carbon and hard carbon coatings with gradient structures, the safety and stability of the battery in high temperature environments can be further improved, and the structural cracking problem caused by temperature changes can be reduced. Fifth, the combination of graphite carrier and gradient coating can achieve better material matching. The soft carbon and hard carbon content of the gradient coating gradually changes from the inside to the outside, which can effectively reduce the interfacial stress between the coating and the graphite carrier, enhance the bonding strength between the two, and further improve the overall performance of the material. Sixth, due to the layered structure of graphite, it can provide abundant lithium ion embedding and de-embedding sites. Combined with the optimized design of the coating, the desolvation ability of lithium ions can be effectively improved, thereby improving the charging performance of the battery. Seventh, graphite has good stability at different temperatures. With the gradual structure of soft carbon and hard carbon in the coating, the temperature coefficient of the battery (such as 25℃ discharge capacity / 45℃ discharge capacity) can be further optimized, and the performance consistency of the battery at different ambient temperatures can be enhanced. Therefore, the use of graphite as a carrier of the negative electrode material can not only take advantage of its excellent conductivity and specific capacity, but also further improve the conductivity, cycle stability and thermal stability of the battery by combining with the gradient coating. This design makes the negative electrode material perform well in high rate performance, long cycle life and high temperature stability, and has significant practical application advantages. In the field of energy storage, this negative electrode material is expected to be used in high-performance lithium-ion batteries, providing higher energy density and better user experience.

[0038] It should be noted that the content of soft carbon material gradually decreases from the inside to the outside, and the content of hard carbon material gradually increases from the inside to the outside. Here, "inside" refers to the direction close to the carrier, and "outside" refers to the direction away from the carrier and close to the surface of the coating layer.

[0039] It should also be noted that, in the present invention, soft carbon refers to amorphous carbon that can be graphitized at a high temperature of 2500°C or above, and hard carbon refers to amorphous carbon that is difficult to graphitize at a temperature of 3000°C or above.

[0040] In combination with the first aspect, in some embodiments of the present invention, channels are distributed in the coating layer.

[0041] In combination with the first aspect, in some embodiments of the present invention, the channel is a funnel-shaped structure that is narrow inside and wide outside.

[0042] It should also be noted that the pores are funnel-shaped structures that are narrow inside and wide outside, where "inside" refers to the direction close to the carrier, and "outside" refers to the direction away from the carrier and close to the surface of the coating layer.

[0043] The funnel-shaped pore structure can effectively improve the transmission efficiency of ions. Due to the narrow inner and wide outer design of the pore, lithium ions can quickly enter and leave a larger area of ​​the pore during the battery charging and discharging process, thereby reducing the diffusion path of ions in the negative electrode material. This design can speed up the transmission speed of lithium ions and improve the battery's charging and discharging rate and rate performance. Furthermore, the funnel-shaped pore structure makes the electron conduction path more efficient. The narrower pores inside can reduce the obstacles to electrons during transmission, while the wider pores outside help reduce the interface resistance with the coating layer. This structure can improve the overall conductivity of the negative electrode material, thereby improving the power performance and current carrying capacity of the battery. Furthermore, the funnel-shaped pore structure can also effectively reduce the resistance during the insertion and extraction of lithium ions. Since the design of the pore allows ions to flow more smoothly, this can improve the charging and discharging performance of the material, especially under high-rate charging and discharging conditions. In addition, during the charging and discharging process, the funnel-shaped pore structure can relieve the stress caused by volume change, thereby reducing the structural damage of the material. This helps to extend the cycle life of the negative electrode material and improve the stability and durability of the battery. Furthermore, the funnel-shaped pore structure can help reduce the thermal expansion problem caused by temperature changes. The pore design enables the material to better adapt to volume changes in high or low temperature environments, thereby improving the performance stability of the battery at different temperatures. Furthermore, the design of the funnel-shaped pore can effectively improve the desolvation ability of lithium ions in the negative electrode material. Because the pore structure helps ions to be more evenly distributed and transported in the material, this can improve the efficiency of lithium ion deintercalation, thereby improving the charging performance of the battery. Combining the advantages of the funnel-shaped pore, the design can effectively optimize the various performance indicators of the negative electrode material, including capacity, conductivity, rate performance and cycle stability. By improving the efficiency of ion transport and electronic conductive paths, the comprehensive performance of the negative electrode material is significantly improved, thereby enhancing the overall performance of the battery. As a result, the funnel-shaped pore structure with narrow inside and wide outside provides significant performance advantages for the negative electrode material. This structure optimizes ion transport and electronic conductive paths, improves the charge and discharge efficiency, rate performance and cycle stability of the battery, and enhances the adaptability of the material under different temperature conditions. This innovative pore structure enables negative electrode materials to show broader application prospects in the field of energy storage, especially in high-performance lithium-ion batteries, which can provide higher energy density.

[0044] In combination with the first aspect, in some embodiments of the present invention, the pore size b of the pore channel, the thickness h of the coating layer, and the particle size a of the carrier satisfy the relationship: b = h / 100 + a × 10 -5 , where a ranges from 5 μm to 10 μm, and h ranges from 30 nm to 80 nm.

[0045] The above relationship ensures that the size of the pores is reasonably matched with the coating thickness and the carrier particle size, which helps to optimize the transmission path of lithium ions. The pore size is designed to be within a moderate range, which helps to increase the diffusion rate of lithium ions and reduce the ion transmission resistance, thereby improving the charge and discharge efficiency and rate performance of the battery. Specifically:

[0046] The reasonable size of the pores allows lithium ions to migrate smoothly in the negative electrode material. This design optimizes the battery charging process, making it easier for lithium ions to be inserted or removed, thereby improving the charging rate and overall charging performance of the material.

[0047] The pore size designed according to the relationship can effectively reduce the mechanical stress caused by volume change during charging and discharging, thereby reducing the risk of structural damage. Appropriate pore size helps alleviate the problems caused by volume expansion or contraction and prolongs the cycle life of the negative electrode material.

[0048] The design of the pores also affects the conduction path of electrons in the negative electrode material. By optimizing the size of the pores, the path resistance of electron transmission can be reduced, the overall conductivity of the material can be improved, and thus the power performance of the battery can be improved.

[0049] The relationship between pore size, coating thickness and carrier particle size can ensure that the negative electrode material has high consistency in different batches. This consistency helps to maintain the stability and reliability of battery performance in practical applications.

[0050] In addition, reasonable pore design helps the material remain stable under high temperature conditions. Appropriate pore size can reduce material deformation caused by thermal expansion, thereby enhancing the stability and safety of the battery in high temperature environments.

[0051] By setting the relationship between the size of the pores, the thickness of the coating layer and the particle size of the carrier, the microstructure of the negative electrode material can be effectively designed to achieve the best balance in functionality. This helps to improve the overall performance of the negative electrode material, including specific capacity, rate performance and cycle life.

[0052] Therefore, the relationship between the pore size b of the pore channel, the thickness h of the coating layer and the particle size a of the carrier is: b = h / 100 + a × 10 -5 , which can significantly improve the performance of negative electrode materials. By optimizing the pore design, the battery's ion transmission efficiency, charging performance, cycle stability and thermal stability can be effectively improved, thereby providing better battery performance and broader application prospects in the field of energy storage.

[0053] In the second aspect, some embodiments of the present invention provide a method for preparing the negative electrode material of the first aspect of the present invention, comprising the steps of mixing a soft carbon source and a hard carbon source to prepare a coating agent, and then coating the carrier by spraying.

[0054] It can be understood that the preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize. The simple preparation process also greatly improves the consistency and repeatability of production. This gradient material with a coating layer will promote the application of negative electrode materials in the lithium ion battery industry.

[0055] In combination with the second aspect, in some embodiments of the present invention, the spraying time t and the mass percentage X of the soft carbon source in the coating agent and the mass percentage Y of the hard carbon source in the coating agent satisfy the relationship: X=1 / (t+1), X+Y=1.

[0056] As time goes by, that is, the thickness of the coating layer increases, the content of soft carbon source decreases and the content of hard carbon source increases. After carbonization treatment, a funnel-shaped gradient coating structure with narrow pores inside and wide pores outside is formed. The coating layer has both ordered and disordered structures, and has both soft carbon and hard carbon properties. Compared with traditional liquid phase coating, the rate performance is greatly improved.

[0057] Specifically, this relationship ensures that the ratio of soft carbon and hard carbon materials in the coating changes with the increase of spraying time. This design forms a funnel-shaped gradient coating structure that is narrow inside and wide outside, with a higher soft carbon content inside and a higher hard carbon content outside. After carbonization treatment, this gradient structure can effectively combine the advantages of soft carbon and hard carbon to improve the overall performance of the negative electrode material. The soft carbon layer in the gradient coating structure provides excellent conductivity and good interface bonding, while the external hard carbon layer provides a larger degree of disorder and interlayer spacing, which is beneficial to improving the charging performance of the material. As the spraying time increases, the hard carbon content of the coating increases, which makes the material have better performance at high-rate charge and discharge, and the performance is significantly improved compared to the traditional liquid phase coating method.

[0058] As the spraying time increases, the thickness of the coating increases, and the content of hard carbon increases, which helps to reduce the structural damage caused by volume changes during battery charging and discharging. The gradient structure can effectively disperse stress, improve the stability of the material under high temperature and high pressure environment, and prevent structural cracking problems. In addition, the production cost is reduced by a simple spraying process instead of complex equipment or harsh reaction conditions. The relationship between spraying time and material ratio allows for simplified process control, and the raw materials are easily available, making the production process more economical and efficient, suitable for industrial large-scale production. Using the relationship between spraying time and material ratio, the composition and thickness of the coating can be accurately controlled, thereby improving the consistency and repeatability of production. This consistency is crucial for industrial production and helps ensure that the performance of each batch of products is stable and meets the requirements of commercial applications. The gradient coating combines the advantages of soft carbon and hard carbon, which significantly improves the conductivity, charging performance, rate performance and cycle stability of the negative electrode material. The coating after carbonization can effectively balance the ordered and disordered structures, improve the comprehensive performance of the material, and make its application in lithium-ion batteries more extensive and efficient.

[0059] In combination with the second aspect, in some embodiments of the present invention, the soft carbon source includes at least one of polyurethane resin, styrene resin, phenolic resin, epoxy resin, amide resin, polyimide resin, silicone resin, cycloolefin resin and asphalt.

[0060] In a third aspect, in some embodiments of the present invention, a lithium-ion battery is provided, comprising the negative electrode material of the first aspect of the present invention or the negative electrode material prepared by the method of the second aspect of the present invention.

[0061] It can be understood that the lithium ion battery of the present invention, due to the use of the negative electrode material of the present invention, has all the beneficial effects of the negative electrode material, specifically:

[0062] In terms of improving conductivity, due to the presence of soft carbon materials in the coating layer, the conductivity of the battery is significantly improved, which helps to improve the battery's charging and discharging efficiency and power performance.

[0063] In terms of enhancing cycle performance, the gradient coating structure makes the material and the substrate more compatible, reducing the structural cracking problem caused by the mismatch between the coating layer and the substrate, thereby increasing the cycle life of the battery.

[0064] In terms of optimizing rate performance, the gradual incremental design of hard carbon materials helps to improve the charging performance of the materials, allowing the battery to maintain a higher capacity and stability during high-rate discharge.

[0065] In terms of improving temperature stability, by improving the temperature coefficient, the discharge capacity of the battery under different temperature conditions (such as 25°C and 45°C) maintains good consistency, enhancing the battery's temperature adaptability.

[0066] In terms of improving safety performance, the design of the gradient coating reduces the safety hazards caused by the difference in properties between the coating and the substrate, and exhibits better stability under high temperature and high pressure environments.

[0067] The above improvements enable lithium-ion batteries containing the negative electrode material to have better overall performance and broader application prospects in the field of energy storage.

[0068] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0069] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0070] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0071] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0072] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0073] Example 1

[0074] A negative electrode material is prepared, specifically:

[0075] Select pure secondary particles, graphite with an aggregate particle size of 7 μm as the carrier; it should be noted that pure secondary particles have a smaller expansion and a slightly larger OI value (Oxidation Index), and generally this component accounts for the majority of fast-filling graphite. In the present invention, single particles (primary particles) can also be used without significant impact;

[0076] A soft carbon source and a hard carbon source are selected to be mixed to prepare a coating agent, wherein the soft carbon source is asphalt and the hard carbon source is phenolic resin. The mixing method is: a spray coating machine is used for spray coating, ethanol is added to dilute the coating agent, the spray time is 5 minutes, the spray speed is 1kg / min, the mass of graphite and the coating agent is 45kg±1kg and 3.5±0.2kg, and the speed of the spray coating machine is 600±50r / min;

[0077] The graphite is coated by spraying. As the spraying time changes, the ratio of the soft carbon source and the hard carbon source of the coating agent also changes, thus forming a concentration gradient. In actual operation, the hard carbon source and the soft carbon coating agent are diluted by two reactors respectively, and then the outflow rate of the hard carbon source and the soft carbon source in the two reactors is controlled. After flowing out, they enter a reactor for mixing, and then spray. Among them, the whole process is continuous production, and the outflow rate of the soft carbon source and the hard carbon source is variable, satisfying X=1 / (t+1), X+Y=1. A total of 3.5KG of asphalt and resin are coated on the graphite. Control the outflow rate of the hard carbon, which changes with time, so that the ratio of the two can be controlled, Vx=1 / 5kg / min; Vy=t / 5kg / min, and the integral is calculated. The sum of the two is exactly 3.5kg.

[0078] The concentration formula is: X = 1 / (t+1), X + Y = 1, where t is the spraying time of 5 min, X is the mass fraction of the soft carbon source in the coating agent, and Y is the mass fraction of the hard carbon source in the coating agent; a is the aggregate particle size of graphite; the coating layer thickness h is 50 nm, and the pore size b = h / 100 + a × 10 -5 , with the change of coating layer thickness h, it is between 0.07 and 0.57 nm, and gradually increases from the inside to the outside. The coating layer thickness h refers to the distance from a specific position in the coating layer to the carrier surface.

[0079] Example 2

[0080] A negative electrode material was prepared in the same manner as in Example 1, except that the graphite aggregate particle size was changed to 5 μm; the pore size b = h / 100 + a × 10 -5 , with the change of coating layer thickness h, it is between 0.05 and 0.57 nm, and gradually increases from the inside to the outside. The coating layer thickness h refers to the distance from a specific position in the coating layer to the carrier surface.

[0081] Example 3

[0082] A negative electrode material was prepared in the same manner as in Example 1, except that the particle size of the graphite aggregate was changed to 10 μm; the pore size b = h / 100 + a × 10 -5, with the change of coating layer thickness h, it is between 0.1 and 0.6 nm, and gradually increases from the inside to the outside. The coating layer thickness h refers to the distance from a specific position in the coating layer to the carrier surface.

[0083] Example 4

[0084] A negative electrode material was prepared in the same manner as in Example 1, except that the coating layer thickness h was 30 nm, and the pore size b = h / 100 + a × 10 -5 , with the change of coating layer thickness h, it is between 0.07 and 0.37 nm, and gradually increases from the inside to the outside. The coating layer thickness h refers to the distance from a specific position in the coating layer to the carrier surface.

[0085] Example 5

[0086] A negative electrode material was prepared in the same manner as in Example 1, except that the coating layer thickness h was 80 nm, and the pore size b = h / 100 + a × 10 -5 , with the change of coating layer thickness h, it is between 0.07 and 0.87 nm, and gradually increases from the inside to the outside. The coating layer thickness h refers to the distance from a specific position in the coating layer to the carrier surface.

[0087] Comparative Example 1

[0088] A negative electrode material was prepared in the same manner as in Example 1, except that it was coated with pure soft carbon and the pore size b of the pores was a constant value of 0.07.

[0089] Comparative Example 2

[0090] A negative electrode material was prepared in the same manner as in Example 1, except that it was coated with pure hard carbon and the pore size b was a constant value of 0.57.

[0091] Comparative Example 3

[0092] A negative electrode material was prepared in the same manner as in Example 1, except that no coating was performed.

[0093] Comparative Example 4

[0094] A negative electrode material was prepared, which was consistent with the preparation method of Example 1, except that no gradient coating was used, and hard carbon and soft carbon were directly mixed in a ratio of 1:1 and directly coated.

[0095] Assembling the battery

[0096] Negative electrode sheet preparation:

[0097] The negative electrode active material, conductive agent (SP and CNT mixed in a mass ratio of 0.45:0.05), and binder (SBR and PAALi mixed in a mass ratio of 0.5:1.8) are mixed in a weight ratio of 97.7:1.1:1.2 to obtain an anode active material slurry, which is evenly coated on the negative electrode collector, and then cold pressed and slit to obtain the negative electrode sheet.

[0098] Preparation of positive electrode:

[0099] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, and the solvent NMP is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0100] Preparation of electrolyte:

[0101] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0102] Separation film: A polyethylene film is selected as the separation film.

[0103] Preparation of lithium-ion battery: The above positive electrode sheet, isolation membrane, and negative electrode sheet are 5000mAh, and the design value is 1C=5000mA.

[0104] Performance Testing

[0105] The RT lithium precipitation, hot box and temperature coefficient of the negative electrode materials prepared in the embodiment and the comparative example were tested respectively. Among them, the test method of RT lithium precipitation is:

[0106] RT2.8C / 0.7C lithium plating: ① Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0107] RT2.6C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0108] RT2.4C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.4C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.4C constant current and constant voltage, cut-off rate 0.025C, and leave for 5min; ⑤ Disassemble the interface;

[0109] RT2.2C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and leave for 5min; ② Discharge to 3V at 0.7C constant current, and leave for 5min; Repeat steps ① to ② 49 times in total; ④ Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and leave for 5min; ⑤ Disassemble the interface.

[0110] The test method for hot box performance is as follows: discharge at a constant current of 0.2C, with a cut-off voltage of 3.0V; leave for 5 minutes; charge to 4.50V at a constant current and voltage of 0.5C, with a cut-off rate of 0.02C; put the battery cell into the oven, and increase the oven temperature from 20±5℃ to 13X±2℃ at a rate of 5±2℃ / min, and keep it at 13x±2℃ for 60 minutes before stopping. During the test, the surface temperature of the battery cell, the oven temperature and the battery cell voltage need to be monitored; the test is considered passed if there is no leakage, no rupture, no smoke, no fire, and no explosion.

[0111] The testing method of temperature coefficient is as follows: incubator temperature 25℃; stand for 120min; charge to 4.50V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C; stand for 10min; discharge at 0.2C constant current, with a cut-off voltage of 3V; record the discharge capacity of the battery cell at 25℃; incubator temperature 45℃; stand for 120min; charge to 4.50V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C; stand for 10min; discharge at 0.2C constant current, with a cut-off voltage of 3V; record the discharge capacity of the battery cell at 45℃; temperature coefficient = discharge capacity at 25℃ / discharge capacity at 45℃.

[0112] The results are shown in Tables 1 to 3.

[0113] Table 1 RT lithium precipitation test results

[0114] Group 2.2C 2.4C 2.6C 2.8C Example 1 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 2 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 3 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Example 4 No lithium precipitation No lithium precipitation No lithium precipitation Slight lithium deposition Example 5 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Comparative Example 1 No lithium precipitation No lithium precipitation Slight lithium deposition Lithium Separation Comparative Example 2 No lithium precipitation No lithium precipitation No lithium precipitation No lithium precipitation Comparative Example 3 No lithium precipitation Slight lithium deposition Lithium Separation Severe lithium deposition

[0115] As can be seen from Table 1, by comparing Example 1 with Comparative Examples 1 and 3, the soft and hard carbon gradient coating has a higher lithium precipitation window than pure soft carbon coating or no coating. This is because the disorder degree and interlayer spacing of hard carbon are larger than those of soft carbon, which is beneficial to improving the charging performance of the material. Using hard carbon as an outer coating agent plays a good ion conductive role.

[0116] Table 2 Hot box performance

[0117]

[0118]

[0119] As can be seen from Table 2, comparing Example 1 and Comparative Example 2, the soft and hard carbon gradient coating has a better hot box than the pure hard carbon coating. This is because the hard carbon coating has poor conductivity, poor bonding with the substrate, and is prone to structural defects and side reactions. Using soft carbon as the inner layer can increase the bonding with the substrate, and the gradient structure can make the main material more compatible with the coating layer, preventing structural cracking problems caused by the large gap between the coating layer and the main material in a high temperature and high pressure environment. Secondly, it buffers the side reactions caused by the hard carbon, thereby improving the hot box.

[0120] It should be noted that in Table 2, "3 / 3PASS" means that 3 cells were tested and all 3 cells passed; "1 / 3PASS" means that 3 cells were tested and 1 cell passed, and so on. At the same time, " / " in the table means that the test was not conducted, because the samples did not all pass the lower temperature test in the previous level, so there is no need to conduct the next higher temperature hot box test.

[0121] It should also be noted that the hot box performance of lithium-ion batteries is critical to ensure the safety and efficiency of the battery at different temperatures. Good thermal management can prevent overheating, extend battery life, and improve charging and discharging efficiency, thereby ensuring the reliability and performance of the equipment. In high-power applications, thermal management is particularly important because it prevents thermal runaway and ensures user safety. In Table 2, qualified hot box performance means that no fire or explosion occurred during the test.

[0122] Table 3

[0123]

[0124] As can be seen from Table 3, compared with Example 1 and Comparative Example 4, the funnel-shaped coating structure is beneficial to improving the ion conduction efficiency, can improve the low-temperature lithium ion desolvation ability, improve the temperature coefficient (25°C discharge capacity / 45°C discharge capacity), and avoid the formation of lithium crystals.

[0125] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A negative electrode material, characterized in that: It comprises a carrier and a coating layer which at least partially covers the surface of the carrier, wherein the coating layer contains soft carbon material and hard carbon material, wherein the content of the soft carbon material gradually decreases from the inside to the outside, and the content of the hard carbon material gradually increases from the inside to the outside.

2. The negative electrode material according to claim 1, characterized in that The support includes graphite.

3. The negative electrode material according to claim 1, characterized in that The coating layer is distributed with pores.

4. The negative electrode material according to claim 3, characterized in that The hole is a funnel-shaped structure that is narrow inside and wide outside.

5. The negative electrode material according to claim 4, characterized in that The relationship between the pore size b of the pores, the thickness h of the coating layer and the particle size a of the carrier is: b = h / 100 + a × 10 -5 , where a ranges from 5 μm to 10 μm, and h ranges from 30 nm to 80 nm.

6. A method for preparing the negative electrode material according to any one of claims 1 to 5, characterized in that: The method comprises the steps of mixing a soft carbon source and a hard carbon source to prepare a coating agent, and then coating the carrier by spraying.

7. The method according to claim 6, characterized in that The spraying time t and the mass percentage X of the soft carbon source in the coating agent and the mass percentage Y of the hard carbon source in the coating agent satisfy the relationship: X=1 / (t+1), X+Y=1.

8. The method according to claim 6 or 7, characterized in that: The soft carbon source includes at least one of polyurethane resin, styrene resin, epoxy resin, amide resin, polyimide resin, silicone resin, cycloolefin resin and asphalt.

9. The method according to claim 6 or 7, characterized in that: The hard carbon source includes a phenolic resin.

10. A lithium ion battery, characterized in that: The invention comprises the negative electrode material as described in any one of claims 1 to 5 or the negative electrode material prepared by the method as described in any one of claims 6 to 9.